An Overview of Electronic Publishing and Extensible Markup Language (XML) - John Kane; Joseph R. Makuch (Journal of Applied Communications, 1998)
Many knowledge-based organizations are expanding their publishing efforts to include electronic publishing. This article gives evidence of this move and discusses the factors that have been instrumental in promoting electronic publishing. The importance of information stucture and adherence to open standards are emphasized as critical components of digital document management systems. The development and use of Standard Generalized Markup Language (SGML) and Hypertext Markup Language (HTML) are discussed along with their strengths and weaknesses as tools of electronic publishing. An emerging alternative, Extensible Markup Language (XML), is described as having features that may reduce some of the impediments to producing and managing documents digitally.